The Molecular Design Research Network. (30th August 2017) - Coish, Philip; Brooks, Bryan W; Gallagher, Evan P; Mills, Margaret; Kavanagh, Terrance J; Simcox, Nancy; Lasker, Grace A; Botta, Dianne; Schmuck, Stephanie C; Voutchkova-Kostal, Adelina; Kostal, Jakub; Mullins, Melissa L; et al.
Abstract: Herein, we provide an overview of a research network that is aimed at fostering interdisciplinary collaboration between chemists and toxicologists with the goal of rationally designing safer commercial chemicals. The collaborative is the Molecular Design Research Network (MoDRN) that was created in 2013 with funding from the EPA-National Science Foundation Networks for Sustainable Molecular Design and Synthesis (NSMDS) program. MoDRN is led by 4 universities, Baylor University, University of Washington, The George Washington University, and Yale University. The overarching goal of the network is to enable and empower the design of safer chemicals based on the fourth Principle of Green Chemistry that states, "chemical products should be designed to preserve efficacy of function while minimizing toxicity."